Multi-mode operation and thermo-economic analyses of combined cooling and power systems for recovering waste heat from data centers - Chen, Xiaoting (2022)
Current solutions for waste heat recovery from data centers are mainly district heating and refrigeration. However, intermittent demand for space heating and cooling resulted from seasonal or spatial variations makes inefficient utilization of waste heat. To better harvest the low-grade thermal energy in data centers, combined cooling and power systems are proposed, with the capability of adjusting the energy output to meet diverse energy demands hourly and seasonally. In total, six cogeneration systems with different configurations are investigated, with the power cycles being either organic Rankine cycle or Kalina cycle, and the refrigeration cycles being vapor compression refrigeration cycle, ejector expansion refrigeration cycle or absorption refrigeration cycle. Depending on the energy demands of data centers, each system has three operation modes: combined cooling and power, power alone and cooling alone. The performance is evaluated in terms of both the thermodynamic and economic performance by parametric study and multi-objective optimization. Results show that the organic Rankine cycle/absorption refrigeration cycle hybrid system has the best thermal-economic performance in all three modes. According to the comprehensive evaluation of the TOPSIS method and the entropy weight method, the energy efficiency at the optima is 58.13%, and the unit cost of product is 4.25 $/GJ, with the net power output of 4.25 kW and the cooling capacity of 150 kW.